3.7 billion year old detrital sediments in Greenland are consistent with active plate tectonics in the Eoarchean - Austin Jarl Boyd; Minik T. Rosing; Magnus A. R. Harding; Donald E. Canfield; Tue Hassenkam (Communications Earth & Environment, 2024)
Abstract Plate tectonic processes modulate element cycling, crust generation, and differentiation, yet at what point in Earth’s history these processes emerged remains debated. Here we present evidence that parts of the >3.7 Ga Isua Supracrustal Belt formed within a fore-arc setting, consistent with the operation of plate tectonics in the Eoarchean. We show that the oldest known sequence of detrital meta-sedimentary rocks were deposited conformably above chemical sediments on a volcanic basement. Mineral and trace elemental compositions show that turbiditic and pelagic detrital sediments were derived from terrains, comprising both basalts and differentiated tonalitic igneous rocks. The boninitic volcanic basement would have formed in a tensile environment before the adjacent terrains which sourced the clastic sediments. This suggests formation within a fore-arc during the initial few million years of subduction. This environment may have facilitated the local proliferation of life suggested by the frequent occurrence of layers rich in biogenic graphite.